Health-Related Quality of Life After Elective Surgery: Measurement of Longitudinal Changes - Mangione, Carol M (Blackwell Science Inc, 1997)
OBJECTIVE: To examine the responsiveness of the 36-Item Short Form Health Survey (SF-36) to clinical changes in three surgical groups and to study how health-related quality of life (HRQL) changes with time among patients who undergo total hip arthroplasty, thoracic surgery for treatment of non-small-cell lung cancer, or abdominal aortic aneurysm (AAA) repair. DESIGN: Prospective cohort study with serial evaluations of HRQL preoperatively and at 1, 6, and 12 months after surgery. SETTING: University tertiary care hospital. PATIENTS: Of 528 patients, more than 50 years of age, who were admitted for these elective procedures, 454 (86%) provided preoperative health status data and are members of the study cohort. At 12 months after surgery, 439 (93%) of the cohort was successfully contacted and 390 (90%) provided follow-up interviews. MEASUREMENTS AND MAIN RESULTS: The Medical Outcomes Study SF-36, the Specific Activity Scale, five validated health transition questions, and a 0 to 100 scale measure of global health were used to assess changes in health status at 1, 6, and 12 months after surgery. Change in health status as measured by the SF-36 demonstrated that physical function and role limitations due to physical health problems were worse 1 month after these three surgeries. However, by 6 months after surgery, most patients experienced significant gains in the majority of the dimensions of health, and these gains were sustained at 12 months after surgery. Longitudinal changes in the SF-36 were positively associated with responses to the five health transition questions, to changes on the Specific Activity Scale and global health rating question, and to clinical parameters for persons who had AAA repair. These findings indicate that the SF-36 has evidence of validity and is responsive to expected changes in HRQL after elective surgery for these procedures. CONCLUSIONS: For the total hip arthroplasty patients, responsiveness was greatest for the SF-36 scales that measure physical constructs. However, for the two other procedures and at various points of recovery, significant changes were observed for all eight subscales, suggesting that responsiveness was dependent on the type of surgery and the timing of follow-up, and that multidimensional measures are needed to fully capture changes in HRQL after surgery.